O estudo da teoria das tópicas nas toadas do bumba meu boi: proposta de execução, na guitarra elétrica, das toadas com um grupo de alunos da Escola de Música do Estado do Maranhão “Lilah Lisboa de Araújo” (EMEM) - LIMA, Norlan Aragão (2020)
In this work, I find, in the Bumba meu Boi's "toadas", made in Maranhão, the musical elements that characterize and identify each of the existing types of Bumba meu Boi in the state. With the identification, analysis and understanding of the "tópicas", I configure parameters that make it possible to play the Bumba meu Boi's "toadas" in an electric guitar smoothly. To this end, I present concepts of the note groupings that generate the "tópicas" (common places), the rhythms that are used in the scales, the most commonly used chord progressions, the nuances that make them different from other types of composition. Thus, the understanding of the parameters and the establishment of a systematized knowledge will help in the technical improvement of the teaching and learning of the instrument given in the Electric Guitar course of the Escola de Música do Estado do Maranhão “Lilah Lisboa de Araújo (EMEM)” and in other establishments of music teaching. In this work, I will consider only the accents of Pindaré or Baixada, Ilha or Matraca and Orquestra to develop the research that I proposed. I will base my ideas on Aristotle's concepts of Rhetorical Art, in the discourse of musical language, from the understandings of Leonard Ratner, V. Kofi Agawu and Acácio Piedade that music can be identified through the “Tópicas” (small fragments that characterize it and that refer to its place of origin). The research result will be presented by a group of selected students who will read the musical transcripts emphasizing the "tópicas" characteristics of each accent. The methodology used is the social scientific, based on the alterity and multiple meanings of this musical culture that engages the community and society in an interactive and inclusive way of the direct and indirect characters of this celebration. In the analysis of the work, we verified that the concepts of Leonard Ratner and Acácio Piedade can be used for the investigation of "tópicas" in Maranhão's music. In the harmonic analysis, I will describe the musical chord using Functional Harmonic’s nomenclature, which is usual in the popular music.